2004
DOI: 10.1161/01.atv.0000145016.69181.fa
|View full text |Cite
|
Sign up to set email alerts
|

Carvedilol Inhibits Tumor Necrosis Factor-α–Induced Endothelial Transcription Factor Activation, Adhesion Molecule Expression, and Adhesiveness to Human Mononuclear Cells

Abstract: Objective-We tested the hypothesis that carvedilol, a ␤-adrenoceptor and ␣-adrenoceptor antagonist with potent antioxidant property, could inhibit tumor necrosis factor-␣ (TNF-␣)-induced endothelial adhesiveness to human mononuclear cells (MNCs), an early sign of atherogenesis. Methods and Results-Circulating MNCs were isolated from the peripheral blood of healthy subjects. Compared with control condition, pretreatment of carvedilol (10 mol/L for 18 hours) or probucol (5 mol/L for 18 hours), but not propanolol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 45 publications
3
37
0
Order By: Relevance
“…22,23 Until now, evidence from experimental studies to support the iron hypothesis was fragmentary and contradictory. intravenous iron preparations inhibited proliferation and promoted apoptosis of cultured endothelial cells 24,25 as well as increased MNC-endothelial adhesion in vitro 6,26 ; however, a reliable cell model for atherogenesis [27][28][29] and the exact signaling pathway have not been fully established. Li and Frei 30 have found that iron increased endothelial NOx activity and ROS production in cultured endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 Until now, evidence from experimental studies to support the iron hypothesis was fragmentary and contradictory. intravenous iron preparations inhibited proliferation and promoted apoptosis of cultured endothelial cells 24,25 as well as increased MNC-endothelial adhesion in vitro 6,26 ; however, a reliable cell model for atherogenesis [27][28][29] and the exact signaling pathway have not been fully established. Li and Frei 30 have found that iron increased endothelial NOx activity and ROS production in cultured endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ROS is thought to induce endothelial damage through activation of NF-kB, a major redox-sensitive transcription factor that is a key regulator of cytokines, chemokines, and cellular adhesion molecules. 29,31 Moreover, the signal mechanisms of ROS with vascular inflammation have been documented. 32 Previous studies proposed the hypothesis that iron is a pro-oxidant provoking intracellular ROS production, which may induce redox-sensitive transcription pathway activation and adhesion molecule expression, subsequently promoting MNCendothelial adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been also demonstrated that various substances with antioxidant activities, such as PD 098063 (Wolle et al, 1996), probucol (Chen et al, 2003(Chen et al, , 2004, ginkgo biloba extract (Chen et al, 2003) and carvedilol (Chen et al, 2004) inhibit endothelial adhesiveness to monocytes by reducing VCAM-1 expression via suppression of NF-κB signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analyses were performed as described previously [23,24]. Briefly, the 25- to 40-µg protein subjected to 12% SDS-polyacrylamide gel electrophoresis was transferred onto PVDF membranes and then underwent blotting.…”
Section: Methodsmentioning
confidence: 99%